Genome editing in neurosciences - Jaenisch, Rudolf; Zhang, Feng, 1982-; Gage, F. 1950- (Springer, 2017)
This book is open access under a CC BY 4.0 license. Innovations in molecular biology are allowing neuroscientists to study the brain with unprecedented resolution, from the level of single molecules to integrated gene circuits. Chief among these innovations is the CRISPR-Cas genome editing technology, which has the precision and scalability to tackle the complexity of the brain. This Colloque Médecine et Recherche has brought together experts from around the world that are applying genome editing to address important challenges in neuroscience, including basic biology in model organisms that has the power to reveal systems-level insight into how the nervous system develops and functions as well as research focused on understanding and treating human neurological disorders.
Keywords: Neurogenetics.; Genetic engineering.; RNA editing.; elektronické knihy; electronic books